THE FREQUENCY OF ADVERSE EVENTS AMONG PEDIATRIC INPATIENTS IN THE MATERNITY AND CHILDREN TEACHING HOSPITAL IN AL-DIWANIYAH - Al-Shamsi, Mohammed Mugar Resen; Atyah, Ayad Raheem; Almayyahi, Mokhles Mahdi Abolewaikh (International Journal of Psychosocial Rehabilitation, 2020)
An important indicator of the pediatric patient safety is the rate of adverse events (AEs) among in-hospital pediatric patients. AEs are an important cause of morbidity and mortality for pediatric inpatients.Population and methods-A prospective study was performed on admissions to the Maternity and Pediatrics Teaching Hospital in Al-Diwaniyah( Iraq, 180 km south of Baghdad) from January 1st to June 30th, 2019. All patients were followed-up to document the duration of hospitalization, and the degree of harm at discharge. Daily visits to all wards were carried out for recording demographic information and duration of hospitalization, history of chronic conditions, and excluding those out of this study. A total of 3772 were admissions to the hospital during the study period. Data were spread into worksheet of Microsoft Office Excel 2016 for subsequent analysis.Results-In this study, a 356 (9.4 %) from 3772 patients found to have AEs. AEs occurred in 16 (4.5 %) patients admitted for up to 5 days, 122 (34.3%) patients admitted for 6 - 10 days, and 218 (61.2 %) patients admitted for > 10 days (p value = 0.001, significant). Neonates, whether admitted to neonatal intensive care unit or nursery care unit, were more commonly afflicted by AEs. AEs occurred in 115 (32.3 %) out of 356 patients with AEs (p value = 0.008).Another statistically significant value (p value = 0.001) was found in the distribution of AEs among patients of specific wards, namely neona tal intensive care unit (NICU), nursery care unit (NCU), PICU, isolationward, and surgicalward. AEs occurred in 41 (11.5 %) patients in neonatal intensive care unit, 67 (18.8%) patients in nursery care unit, 15 (4.2 %) patients in pediatric intensive care unit, 23 (6.5 %) patients in isolation ward, and 35 (9.8 %) patients in surgical ward. No other level of significance was found regarding distribution of adverse events according to sex, residence, provisional diagnosis, and past medical history. Four classes of patients with AEs were identified as a result of the degree of harm: 205 (57.6 %) patients whorequired just intervention, 135 (37.9 %) patients who required intervention with prolonged hospital stay,5 (1.4 %) patients with disability at time of discharge, and 11 (3.1 %) patients who died from AE. Conclusion-The rate of AEs from provision of medical care in our hospital was high and did not seem to be different from that in other studies around the world. AEs incidence rate was common in neonates admitted either to neonatal intensive care unit or to nursery care unit, in patients with longer duration of hospitalization, and in patients from pediatric intensive care unit, and isolation and surgical wards.